Blood pressure reduction and outcome after endovascular therapy with successful reperfusion: a multicenter study. (5th December 2019) - Anadani, Mohammad; Arthur, Adam S; Alawieh, Ali; Orabi, Yser; Alexandrov, Andrei; Goyal, Nitin; Psychogios, Marios-Nikos; Maier, Ilko; Kim, Joon-tae; Keyrouz, Saleh G; de Havenon, Adam; Petersen, Nils H; et al.
Abstract : Background: Elevated systolic blood pressure (SBP) after mechanical thrombectomy (MT) correlates with worse outcome. However, the association between SBP reduction (SBPr) and outcome after successful reperfusion with MT is not well established. Objective: To investigate the association between SBPr in the first 24 hours after successful reperfusion and the functional and safety outcomes of MT. Methods: A multicenter retrospective study, which included 10 comprehensive stroke centers, was carried out. Patients with acute ischemic stroke and anterior circulation large vessel occlusions who achieved successful reperfusion via MT were included. SBPr was calculated using the formula 100×([admission SBP−mean SBP]/admission SBP). Poor outcome was defined as a modified Rankin Scale (mRS) score of 3–6 at 90 days. Safety endpoints included symptomatic intracerebral hemorrhage, mortality, and requirement for hemicraniectomy during admission. A generalized mixed linear model was used to study the association between SBPr and outcomes. Results: A total of 1361 patients were included in the final analysis. SBPr as a continuous variable was inversely associated with poor outcome (OR=0.97; 95% CI 0.95 to 0.98; p<0.001) but not with the safety outcomes. Subanalysis based on reperfusion status showed that SBPr was associated with lower odds of poor outcome only in patients with complete reperfusion (modified Thrombolysis in Cerebral Infarction (mTICI 3)) but not in patients with incomplete reperfusion (mTICI 2b). When SBPr was divided into categories (<1%, 1%–10%, 11%–20%, >20%), the rate of poor outcome was highest in the first group. Conclusion: SBPr in the first 24 hours after successful reperfusion was inversely associated with poor outcome. No association between SBPr and safety outcome was found.